IMPACT OF A CONDUSIVE WORK ENVIRONMENTS TO HIGH EMPLOYEE PERFORMANCE - Oktafien, Shinta; Budi Santoso, Anton; Roespinoedji, Roeshartono (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how much influence the work environment is conducive to high employee performance at PT. Taspen (Persero) Bandung Main Branch Office. In this study, the population is all employees who work at PT. Taspen (Persero) KCU Bandung with a total sample of 46 employees. For the sampling technique used in this study is the census sample method, which means the number of samples taken is the whole of the total population. Meanwhile, the research method used is a descriptive verification method with a quantitative approach. As for the results of his research indicate that a conducive work environment has a significant influence on the high employee performance at PT. Taspen (Persero) KCU Bandung. This shows that when an organization is able to create a conducive work environment, employees can also show more productive work results.